2019
DOI: 10.1007/s11295-019-1376-z
|View full text |Cite
|
Sign up to set email alerts
|

Transcriptome-wide analysis to dissect the transcription factors orchestrating the phase change from vegetative to reproductive development in Larix kaempferi

Abstract: The timing of phase change from vegetative to reproductive development during aging of forest trees is important for wood and seed production. In a previous study, we investigated the effects of aging on wood formation by measuring the transcriptomic changes in the uppermost main stems of 1-, 2-, 5-, 10-, 25-, and 50-year-old Larix kaempferi. Based on the published transcriptome data, here we investigated the transcriptomic differences between the juvenile vegetative (1-and 2-year-old) and adult reproductive (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 46 publications
(70 reference statements)
0
12
0
Order By: Relevance
“…Many genes have been found to function in plant aging, some of which promote maturation, such as Suppressor of Overexpression of Constans 1 (SOC1) [8], APETALA1 (AP1) [9], Squamosa-Promoter Binding Protein-Like (SPL) [10], and DAL1 (a MADS-box gene) [11], and some delay maturation or maintain the juvenile state, such as microRNA miR156 [12], miR171 [13], Tempranillo (TEM) [14], Terminal Flower 1 (TFL1) [15], MdTFL1 and MdTFL1a [16], Juvenile-to-Adult transition (JAT) [17], LaAP2L1 (a heterosis-associated AP2/EREBP transcription factor from Larix) [18], and Picea abies APETALA2-like genes [19]. In our previous study, 27 age-related transcripts were found to be expressed differentially in stems between the juvenile vegetative (1-and 2-year-old) and adult reproductive (25-and 50-year-old) phases of L. kaempferi, and some of them are homologous to the genes noted above (Figure 1), indicating that they might have similar functions in aging; meanwhile, they may be useful as molecular markers to determine the state of plants [20]. Together, these findings not only aid studies of the molecular mechanisms of aging and rejuvenation, but also provide candidate genes as molecular markers to assess the state of plants.…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations
“…Many genes have been found to function in plant aging, some of which promote maturation, such as Suppressor of Overexpression of Constans 1 (SOC1) [8], APETALA1 (AP1) [9], Squamosa-Promoter Binding Protein-Like (SPL) [10], and DAL1 (a MADS-box gene) [11], and some delay maturation or maintain the juvenile state, such as microRNA miR156 [12], miR171 [13], Tempranillo (TEM) [14], Terminal Flower 1 (TFL1) [15], MdTFL1 and MdTFL1a [16], Juvenile-to-Adult transition (JAT) [17], LaAP2L1 (a heterosis-associated AP2/EREBP transcription factor from Larix) [18], and Picea abies APETALA2-like genes [19]. In our previous study, 27 age-related transcripts were found to be expressed differentially in stems between the juvenile vegetative (1-and 2-year-old) and adult reproductive (25-and 50-year-old) phases of L. kaempferi, and some of them are homologous to the genes noted above (Figure 1), indicating that they might have similar functions in aging; meanwhile, they may be useful as molecular markers to determine the state of plants [20]. Together, these findings not only aid studies of the molecular mechanisms of aging and rejuvenation, but also provide candidate genes as molecular markers to assess the state of plants.…”
Section: Introductionmentioning
confidence: 93%
“…The open reading frame (ORF) finder (https://www.ncbi.nlm.nih.gov/orffinder/) was used to identify the ORFs of the 27 transcription factors reported in our previous work [20] (Table 2). Based on the results, primers (Table S1) were designed to clone their full-length cDNA sequences (https://www.ncbi.nlm.nih.gov/tools/primer-blast/) with Platinum ® Taq DNA polymerase (Invitrogen, Carlsbad, CA, USA).…”
Section: Sequence Analysis Full-length Cdna Cloning and Annotationmentioning
confidence: 99%
See 2 more Smart Citations
“…& Zucc. to reveal the molecular basis of the conifer reproductive phase change [1][2][3]. Differentially expressed genes have been identified, and a regulatory network model has been proposed for L. kaempferi based on these genes [3].…”
Section: Introductionmentioning
confidence: 99%